Upaya Pelestarian Musik Talempong Pacik di Kenagarian Lawang Mandahiling - Randi Yolanda; Syeilendra Syeilendra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to describe the system of efforts to preserve talempong pacik music in the Lawang Mandahiling district. This research is classified as qualitative research and the method used is descriptive analysis. The research instrument is the researcher himself as the main instrument. Data collection was carried out through the stages of literature study, observation, interviews, and audio and video recording. The results of this research are that Mr. Zulkarnai is preserving Talempong Pacik music in three ways, namely: 1) Protection, efforts to protect Talempong Pacik music are carried out by holding talempong music training at Mr. Zulkarnai's house. 2) Development, the art of talempong pacik music has now been developed by artists in Tanah Datar Regency, especially in Kenagarian Lawang Mandahiling. 3) Utilization, talempong pacik music has begun to be used to fill events, namely events, batagak galas, mutual cooperation and entertainment at Kenagarian Lawang Mandahiling. Steps to preserve talempopng pacik music in Kenagarian Lawang Mandahiling include: 1) Studying traditional music, 2) Introducing traditional music to the younger generation, 3) Maintaining traditional music, 4) Introducing traditional music to the outside world.